Additive–Subtractive Manufacturing Based on Water-Soluble Sacrificial Layer: High-Adhesion Metal Patterning via Inkjet Printing - Mengyang Su; Jin Huang; Hongxiao Gong; Zihan Zhu; Pan Li; Huagui Wang; Pengbing Zhao; Jianjun Wang; Jie Zhang (Micromachines)
Inkjet printing has become a primary technique for manufacturing flexible and conformal electronics due to its digital control, design flexibility, and material compatibility. However, its direct deposition nature results in weak adhesion between metal films and substrates, as it mainly relies on van der Waals or capillary forces, which severely limits its broader application in these fields. To address this limitation, we proposed an additive–subtractive manufacturing method based on a water-soluble sacrificial layer. First, the sacrificial material is inkjet-printed onto the substrate. Then, ion sputtering is employed to bombard the surface with high-energy ions, enabling metal atoms to embed into the substrate and form a strongly adhered conductive layer. Finally, the substrate is immersed in water, dissolving the sacrificial layer and detaching the undesired metal, thereby achieving selective retention of the conductive pattern. Experimental results demonstrate that the optimized water-soluble material, with tailored viscosity and surface tension, enables a patterning resolution of ±10 μm. The adhesion strength of the sputtered metal layer is 5.2 times greater than that of inkjet-printed silver nanoparticles. This method was further applied to fabricate conductive patterns on a curved surface with a 91 mm radius confirming its feasibility and adaptability for complex 3D surfaces.